KERJASAMA INDONESIA DENGAN UNICEF DALAM MENGURANGI KEKERASAN TERHADAP ANAK DI PROVINSI JAWA TENGAH PERIODE 2011-2015 - Tri Danang Budi Mulyo, - (2018)
Violence against children in Indonesia has increased from year to year. The Indonesian government to build cooperation with UNICEF, an international organization that focuses on children, the study aims to analyze and study the cooperation between Indonesia and UNICEF to reduce violence against children in central Java province in 2011-2015. This is a qualitative approach. This type of research is applied and descriptive. The source of the data used is data promer and secondary interviews, literature or audio recordings-visual, and data modeling program planning deploy the elimination of violence against children long term in Indonesia coming from the ministry of planning and national development, the ministry of social and ministries protection of women and children. Data will be analyzed by using the theory of international cooperation, international organization theory, the concept of violence. Based on data analysis, we concluded that the cooperation of the Indonesian government with UNICEF provides aid learning and planning long term as Program PKH and education programs are child-friendly school teachers and caregivers and program campaign stop violence against children aims to increase public awareness about the dangers of violence against children and reduce violence